ANALISIS KEMAMPUAN LITERASI SAINS PADA SISWA SEKOLAH DASAR - Agits Aulia Rahmah; Resa Respati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the scientific literacy abilities of fifth-grade students in elementary schools, specifically comparing the differences between urban and rural schools. Scientific literacy is defined as the ability to utilize scientific knowledge to identify questions, explore new knowledge, describe scientific phenomena, and draw conclusions based on scientific evidence. The importance of scientific literacy is emphasized in the context of the 21st century, which demands individuals possess superior qualities to compete globally. This research employed a descriptive quantitative approach with a survey method, involving 30 fifth-grade students from two elementary schools (SD A in a rural area and SD B in an urban area). Data were collected through a written test consisting of 20 items. Descriptive analysis results indicate that the majority of students in both schools fall into the